Colonization Ability of Biological Control Agent Tricoderma spp on Cocoa Pod and Seedling - Rina Sriwati; Tjut Khamzurni; Elvira Iskandar; Mitra T. A. Lestari (Syiah Kuala University, 2015)
Some of Trichoderma species as antagonistic fungi are usually considered soil microorganism, They colonize plant roots, some- times forming a symbiotic relationship. Three species of Trichoderma (T. virens, T. harzianum and T. asperellum) have been inoculated on cacao seedling and cocoa pod. Trichoderma species can be re-isolated from surface sterilized cacao seedling, including the stem and leaf, root, and pod then observed their colonization ability. Fungal hyphae were observed under the microscope emerging from the leaf, steam, root of seedling and pod as soon as 1 day after their isolation from surface sterilized cacao seedling and pod. All Trichoderma species were able to enter and make colonization. The highest percentage of colonization occurred in the T. harzianum by 73.3% (leaves), 46.7% (trunk) and 86.7% (roots). While colonization on the skin cocoa pod (epidermis) also has a different percentage, the highest percentage indicated in the treatment of T. harzianum by 63.3%. We conclude that T. harzianum better biological control agent base on their ability to colonize all part of seedling and pod. Trichoderma species into the cacao stem, leaf, root and pod allowing systemic colonization of this tissue.